2005
DOI: 10.1136/ard.2004.029199
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of rheumatoid arthritis in France: 2001

Abstract: Background: Prevalence estimates of rheumatoid arthritis (RA) vary across Europe. Recent estimates in southern European countries showed a lower prevalence than in northern countries. Objectives: To estimate the prevalence of RA in France in a multiregional representative sample in the year 2001. Methods: A two stage random sample was constituted in seven areas (20 counties) from the national telephone directory of households and by the next birthday method in each household. Patientinterviewers, member of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
8

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(84 citation statements)
references
References 14 publications
3
72
0
8
Order By: Relevance
“…Gout may be an important public health concern, and good knowledge of gout epidemiology is needed to assess the health care needs according to the disease burden. As compared with data for rheumatoid arthritis (10), spondyloarthropathy (11), and osteoarthritis (12), there are no recent data on the overall prevalence of gout in France. One older study determined the prevalence of gout in men, but not women, living in Paris, and found a prevalence of 1.1% among men ages 35-39 years and 2.0% among men 40-44 years (13).…”
Section: Introductionmentioning
confidence: 99%
“…Gout may be an important public health concern, and good knowledge of gout epidemiology is needed to assess the health care needs according to the disease burden. As compared with data for rheumatoid arthritis (10), spondyloarthropathy (11), and osteoarthritis (12), there are no recent data on the overall prevalence of gout in France. One older study determined the prevalence of gout in men, but not women, living in Paris, and found a prevalence of 1.1% among men ages 35-39 years and 2.0% among men 40-44 years (13).…”
Section: Introductionmentioning
confidence: 99%
“…RA affects 0.3% to 1% of the population in Western countries 1,2,3 . If untreated, it leads to joint destruction and functional deterioration and considerable alteration of quality of life.…”
mentioning
confidence: 99%
“…[17] Recent studies on RA prevalence in the Mediterranean region and the surrounding areas have also demonstrated lower values than in Northern Europe. The reported prevalence rates were 0.31% in France, [1] 0.33% in Italy, [2] and 0.37% in Turkey. [3] Another study on the prevalence of RA in the Southern part of Hungary (the border area with Serbia) demonstrated a value of 0.37%.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in Central European countries as well in the Mediterranean area demonstrated the prevalence of RA to be between 0.3 and 0.8. [1][2][3][4][5] The reasons for the overall decrease in the number of patients might be related to a better definition of RA, the precise use of classification criteria, the use of the same methodology to investigate the different populations, and extrinsic factors such as better health conditions and improved nutrition and lifestyle.…”
Section: Prevalence Of Rheumatoid Arthritis In Serbiamentioning
confidence: 99%